Association of telomere length and mitochondrial DNA copy number, two biomarkers of biological aging, with the risk of venous thromboembolism. Issue 223 (March 2023) - Vostatek, Rafaela; Hohensinner, Philipp; Nopp, Stephan; Haider, Patrick; Englisch, Cornelia; Pointner, Julia; Pabinger, Ingrid; Ay, Cihan
Abstract: Background: Venous thromboembolism (VTE) is the third most common cardiovascular disease and occurs in all age groups, albeit the risk increases considerably with age. Previous research indicates mitochondrial dysfunction and telomere shortening in cardiovascular aging. However, in the context of VTE this has not been investigated in detail. Aim: We aimed to explore biomarkers reflecting biological aging (i.e. human mitochondrial DNA copy number (mtDNA) and telomere length) and their association with VTE. Methods: mtDNA and telomere length were measured in a case-control study of 116 patients with a history of VTE and 128 age- and sex-matched healthy individuals from isolated blood using a qPCR-based assay kit. Cases had at least one unprovoked VTE event and were enrolled no earlier than 3 months after the last VTE event. Results: The mtDNA copy number was significantly lower in VTE cases compared to controls (median [IQR]: 663 per diploid cells [78.75–2204.5] vs. 2832 per diploid cells [724–4350]; p < 0.001). After adjustment for age, sex, BMI, and smoking, mtDNA copy number was independently associated with VTE risk (odds ratio per increase in 400 mtDNA per diploid cell: 0.889, 95%CI 0.834–0.947). mtDNA copy numbers were significantly different between women and men (2375 [455–3737] women vs. 893 [152–3154] men; p < 0.001). The analysis of telomere length showed no significant difference between patients and healthy controls. Conclusion: Lower mtDNA levels were found in patients with VTE compared to controls, indicating an association of biological aging with risk of VTE.